2023
DOI: 10.1364/prj.479593
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study on size and temporal dependence of micro-LED arrays for display applications

Abstract: Micro-LEDs are one of the most promising candidates for next-generation displays, yet they are inconvenienced by the efficiency reduction induced by the sidewall defects when pursuing further scaled-down device dimensions. We have systematically investigated both the size and temporal dependence of micro-LEDs. Micro-LED arrays with a mesa size ranging from 7 to 100 μm were prepared for display purposes. The luminance and external quantum efficiency (EQE) were measured and discussed. Surprisingly, micro-LED arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…To date, there has been extensive research and development on size-dependent effects of micro-LED arrays for display applications. J. Nie et al reported that the notorious efficiency reduction induced by sidewall defects in small micro-LED arrays could be significantly reduced by applying short-pulse voltages [30]. Z. Wang et al reported guidance for the analysis and repair of sidewall defects to improve the quantum efficiency of micro-LEDs' display [31].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there has been extensive research and development on size-dependent effects of micro-LED arrays for display applications. J. Nie et al reported that the notorious efficiency reduction induced by sidewall defects in small micro-LED arrays could be significantly reduced by applying short-pulse voltages [30]. Z. Wang et al reported guidance for the analysis and repair of sidewall defects to improve the quantum efficiency of micro-LEDs' display [31].…”
Section: Introductionmentioning
confidence: 99%